2011
DOI: 10.1136/ard.2011.153601
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for refractory granulomatosis with polyangiitis (Wegener's granulomatosis): comparison of efficacy in granulomatous versus vasculitic manifestations

Abstract: The overall response rate of refractory GPA to RTX was high (61.3% complete remission or improvement). Response rates of vasculitic manifestations were excellent; failure of response/progress was mostly due to granulomatous manifestations, especially orbital masses. Relapse rates were high (40%) despite maintenance treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
82
4
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(98 citation statements)
references
References 30 publications
5
82
4
7
Order By: Relevance
“…10 R-CHOP (rituximab ϩ cyclophosphamide ϩ hydroxydaunorubicin ϩ vincristine ϩ prednisone/prednisolone) is the most widely used for these types of lymphoma. Moreover, the usefulness of rituximab has also been demonstrated in patients with certain refractory autoimmune diseases, including rheumatoid arthritis, 11 granulomatosis with polyangitis, 12 and antineutrophil cytoplasmic antibody-associated vasculitis. 13 The great success of rituximab is being followed by the development of new monoclonal antibodies to CD20.…”
Section: Introductionmentioning
confidence: 99%
“…10 R-CHOP (rituximab ϩ cyclophosphamide ϩ hydroxydaunorubicin ϩ vincristine ϩ prednisone/prednisolone) is the most widely used for these types of lymphoma. Moreover, the usefulness of rituximab has also been demonstrated in patients with certain refractory autoimmune diseases, including rheumatoid arthritis, 11 granulomatosis with polyangitis, 12 and antineutrophil cytoplasmic antibody-associated vasculitis. 13 The great success of rituximab is being followed by the development of new monoclonal antibodies to CD20.…”
Section: Introductionmentioning
confidence: 99%
“…Again, all patients in this study were refractory to multiple other therapies, and there was no comparison group of similar patients who did not receive RTX. Holle and colleagues compared the efficacy of RTX in refractory GPA patients with vasculitic versus granulomatous manifestations and included 9 patients with limited ENT disease in their cohort of 59 patients (14). The authors concluded that most of the failure to respond to RTX was due to limited efficacy in granulomatous disease; however, this result was again largely driven by lack of response of orbital masses and pachymeningitis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few small studies examining the use of RTX for granulomatous manifestations of GPA (11)(12)(13)(14). These small case series classified all granulomatous manifestations together and reported variable outcomes regarding the effectiveness of RTX for granulomatous GPA.…”
Section: Introductionmentioning
confidence: 99%
“…Half of the patients have chronic renal disease [13,14]. Half of the patients receive RTX in monotherapy [13,14] while the others receive RTX in combination with other immunosuppressive drugs [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…At least 6 AAV patients (1.2%) treated with RTX developed PCP among 516 patients from different cohorts [9][10][11][12][13][14][29][30][31][32] and proved fatal in 2 patients. PCP occurred 2, 3 and 32 months after the last RTX infusion in 3 patients including ours [13,29]. Half of the patients have chronic renal disease [13,14].…”
Section: Discussionmentioning
confidence: 99%